Renal Access by Sonographer versus Urologist during Percutaneous Nephrolithotomy - Wang, Yanbo; Lu, Zhihua; Hu, Jinghai; Wang, Xiaoqing; Lu, Ji; Hao, Yuanyuan; Wang, Yan; Chen, Qihui; Jiang, Fengming; Zhang, Haifeng; et al. (Urology Journal, 2014)
Purpose: <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">To evaluate the percutaneous access outcomes and complications following percutaneous <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">nephrolithotomy (PCNL) that was obtained by sonographer or urologist at a single academic <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">institution. Material and Methods: <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">A retrospective chart review of 259 patients who underwent PCNL was <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">performed. Patients were stratified according to percutaneous access by sonographer (group 1) or <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">urologist (group 2) in 174 and 85 patients, respectively. Demographic, stone characteristics, operative <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">variables, percutaneous access complications and stone-free rates were compared between <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">groups. Results: <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">The major complication rate and minor complication rate, mean blood loss and rates of <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">blood transfusion were comparable between groups. Compared with urologist, sonographer preferred <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">to choose subcostal rib puncture instead of intercostal rib puncture. The lower calyx was <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">the most frequent site of target calyx puncture in group 1 (165 cases, 94.8%), while the percentage <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">of lower calyx in group 2 was 82.3% (72 cases) (P <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">= .001). The overall stone-free rates were significantly <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">higher in group 2 than that in group 1 (90.6% vs. 79.9%, P <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">= .03). In group 1, 23 cases <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">(13.2%) needed post-operative extracorporeal shock wave lithotripsy (SWL), while, the percentage <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">of post-operative SWL in group 2 was only 4.7% (4 cases) (P <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">= .035). Conclusions: <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">Renal access in PCNL can be safely and successfully obtained by both sonographer <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">and urologist. Infracostal and lower calyx access in our study has poor stone-free rates and sonographer <span style="color: black; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">prefers infracostal and lower access. We encourage urologists establish renal access by <span style="color: black; line-height: 115%; font-family: "Times New Roman","serif"; font-size: 9pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-fareast-font-family: TimesNewRomanPSMT;">themselves during PCNL.